2006
DOI: 10.1002/mats.200500041
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Fracture in Polymer‐Exfoliated Layered Silicate Nanocomposites

Abstract: Summary: The MD technique was used to investigate the fracture behavior in fully exfoliated layered silicate (nanoplatelet)‐polymer nanocomposites. MD results reveal that the addition of the nanoplatelets can improve the fracture strength of polymers. The interactions between the surface of the nanoplatelets and the segments of the polymer, and the relaxation time of polymer chains have significant influences on the fracture strength of the polymer. For polymers with Tg below room temperature, such as polyuret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, many researchers have used MD simulations with non-reactive potentials to investigate fracture related phenomena or to calculate fracture properties. [15][16][17][18][19][20][21][22] For example, Song and Chen 17 used a beadspring model for a polymer with a Lennard-Jones type potential 23 to investigate the fracture behavior in a polymer-exfoliated layered silicate nanocomposite. They concluded that interactions between the surface of the nanoplatelets and segments of the polymer chains, as well M a n u s c r i p t 5 as the relaxation time of polymer chains, significantly influence the fracture strength of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…However, many researchers have used MD simulations with non-reactive potentials to investigate fracture related phenomena or to calculate fracture properties. [15][16][17][18][19][20][21][22] For example, Song and Chen 17 used a beadspring model for a polymer with a Lennard-Jones type potential 23 to investigate the fracture behavior in a polymer-exfoliated layered silicate nanocomposite. They concluded that interactions between the surface of the nanoplatelets and segments of the polymer chains, as well M a n u s c r i p t 5 as the relaxation time of polymer chains, significantly influence the fracture strength of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Classical MD based atomistic analyses of the nanocomposite mechanical deformation as a function of phase morphology are relatively new and have focused on a very limited sets of issues in metallic, polymer-clay, and ceramic nanocomposites. [17][18][19][20][21] Both SiC and Si 3 N 4 have been individually analyzed in the atomistic simulations for different mechanical strength related issues. [22][23][24][25] However, SiC-Si 3 N 4 nanocomposite morphologies are analyzed in this work for the first time for understanding temperature dependent strength.…”
Section: Introductionmentioning
confidence: 99%
“…Models and simulation parameters can be found in ref. [28] Figure 11 shows the simulated stress-strain curves for deformations up to 100% for loading and unloading cycles 1-4. Obviously, the dissipated energy in the first cycle is greater than that in the following cycles, and the dissipated energies were almost the same at second, third and fourth cycles represented by the equal areas as shown in Figure 11.…”
Section: Analysis On the Results Of Computer Simulationmentioning
confidence: 99%